2021
DOI: 10.1007/s15010-021-01639-0
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of anti-SARS-CoV-2 total antibody is higher in younger Austrian blood donors

Abstract: Purpose Frequently the infection with coronavirus 2 (SARS-CoV-2) can be asymptomatic or provoke only mild symptoms. These cases often remain unnoticed, so it is difficult to estimate the actual numbers of infections. Aim of this study was to determine the seroprevalence of anti-SARS-CoV-2 total antibody in Austrian blood donors. Methods 20,228 blood donors aged between 18 and 72 years resident in four Austrian federal states were screened for anti-SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
(26 reference statements)
4
13
0
Order By: Relevance
“…This could potentially correlate with the generally mild courses of disease in our blood donors. Finally, our results are in line with reports from blood donors of four other Austrian federal states [ 16 ], of the Lombardy region in Italy [ 17 ], the San Francisco Bay area in the USA [ 18 ] and recent findings from the Mount Sinai Health System in New York City [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This could potentially correlate with the generally mild courses of disease in our blood donors. Finally, our results are in line with reports from blood donors of four other Austrian federal states [ 16 ], of the Lombardy region in Italy [ 17 ], the San Francisco Bay area in the USA [ 18 ] and recent findings from the Mount Sinai Health System in New York City [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…In summary, SARS-CoV-2 seroprevalence was 3.1% in summer 2020 among Tyrolean blood donors. Our study underscores the suitability of blood donors as an epidemiologic sentinel surveillance system in order to identify local outbreaks and monitor diseases, as blood donors are easily available and representative, at least for the generally healthy subgroup of our population [ 16 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…First responders (4%) had a significantly higher seroprevalence than the general German population (1%) and only 41% were aware that they had COVID-19 in the past [ 5 ]. Our findings corroborate previous findings by determining a higher seroprevalence among first responders of the emergency rescue team, with contact to a COVID-19 case and younger employees [ 6 , 7 ]. The elevated seroprevalence in younger employees may be explained by younger employees being more likely to work in the emergency rescue team and more frequently exposed to someone with COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…All prior population-based seroepidemiological studies in Austria have been conducted in 2020 and hence before vaccination against SARS-CoV-2 was rolled out to the public. These include a first report from our cohort [5] that revealed a seroprevalence of 3.1% (95% CI: 2.7-3.6%) in June to September 2020 in Tyrol and another study [6] in blood donors in four other Federal States of Austria that showed a seroprevalence of 2.5% (2.2-2.7%) in June to December 2020 in four other Federal States of Austria. Furthermore, in November 2020, a nationwide study involving individuals selected based on household sampling found a seroprevalence of 3.1% (95% CI: 2.2-4.0%) [7].…”
Section: Discussionmentioning
confidence: 83%
“…There are several studies in different European countries that have assessed the trajectories of anti-SARS-CoV-2 seroprevalence in the general population over time, including studies in blood donors and household samples in Germany [2] and the UK [3,4]. In Austria, however, previous seroprevalence studies have been restricted to the time before vaccinations against SARS-CoV-2 were licensed [5][6][7] and, hence, data on seroprevalence in the vaccination-era is lacking. Moreover, there are scarce data on the rate at which anti-SARS-CoV-2 antibody levels wane after an infection and after vaccination [8,9].…”
Section: Introductionmentioning
confidence: 99%